An Analysis Of Socio-Cultural Factors Affecting Gender Inequality With A Role In Mental Health (Journal of Pharmaceutical Negative Results, 2023)
Women's needs and expectations in society are changing and evolving now as a result of efforts to reclaim their lost rights and achieve gender justice. In order to understand the cultural-social aspects that contribute to gender disparity, the current research has looked into factors including patriarchal ideology, gender stereotypes, gender socialization, and others. Feminists' conceptions of gender inequality, and Bourdieu's theory have all been used in this study. 385 individuals were chosen as a sample from the married women in Isfahan city who are the statistical population for this study and range in age from 20 to 49. Quota sampling is the technique used in this study. The research's findings show that there is a high level of gender disparity, especially in the economic and cultural spheres, and that there is no correlation between gender stereotypes and inequality, adherence to the patriarchal ideology, or societal norms and inequality. Inequality and gender tolerance exist in the connection.